2021
DOI: 10.1007/s42452-021-04640-2
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study of 1-Bit full adder cells: review, performance comparison and scalability analysis

Abstract: Full Adder (FA) circuits are integral components in the design of Arithmetic Logic Units (ALUs) of modern computing systems. Recently, there have been massive research interests in this area due to the growing need for low-power and high-performance computing systems. Researchers have proposed a variety of FA cells with diverse design techniques, each having its pros and cons. As a result, a systematic method for performance comparison of FA cells using a common simulation platform has become necessary. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…In summary, our estimates indicate that a coherent charge-based full adder in semiconductor quantum dots may have an energetic cost in the tens of meV range. This is an improvement by several orders of magnitude over the best estimates for the cost per bit operation in semiconductor transistor-based technologies, both in modern supercomputers [40] and other full-adder proposals [42]. In comparison with quantum dot cellular automata (QDCA), our estimated energetic cost is two to three orders of magnitude better than other estimates in this field.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In summary, our estimates indicate that a coherent charge-based full adder in semiconductor quantum dots may have an energetic cost in the tens of meV range. This is an improvement by several orders of magnitude over the best estimates for the cost per bit operation in semiconductor transistor-based technologies, both in modern supercomputers [40] and other full-adder proposals [42]. In comparison with quantum dot cellular automata (QDCA), our estimated energetic cost is two to three orders of magnitude better than other estimates in this field.…”
Section: Discussionmentioning
confidence: 70%
“…Recent comprehensive reviews of semiconductor-based full-adders were done in Refs. [41,42] with detailed simulations of their power consumption, delay, and power-delay product (PDP), which quantifies the total energy spent during one gate operation. Overall, in the analysed proposals, the PDP ranges from 1.8 × 10 2 to 1.3 × 10 3 eV for one single-bit addition.…”
Section: B Energetics Of Classical Devicesmentioning
confidence: 99%
“…Based on the design and performance parameters presented in Table 1, it can be observed that QCA FA in [69] has the lowest cell count (22). QCA FA in [81] utilized only 1 more cell than QCA FA in [64].…”
Section: Discussionmentioning
confidence: 99%
“…In binary addition, full adder (1-bit adder) is considered the basic unit cell [19,20]. Moreover, wide word length adders are mainly implemented based on a 1-bit FA cell [21,22]. In addition, diferent arithmetic functions need addition in their internal nodes.…”
Section: Introductionmentioning
confidence: 99%
“…The Gate Diffusion Input (GDI) technique was another circuit design methodology by which logic circuits could be implemented with fewer transistors [15]. However, GDI logic faced the voltage degradation issue [16].…”
Section: Literature Reviewmentioning
confidence: 99%